Structure of the Chemical and Genetic Diversity of the True Lavender over Its Natural Range - Yolande Despinasse; Sandrine Moja; Catherine Soler; Frédéric Jullien; Bernard Pasquier; Jean-Marie Bessière; Sylvie Baudino; Florence Nicolè (Plants, 2020)
The true lavender Lavandula angustifolia Miller is a Mediterranean aromatic shrub widely cultivated for its high quality essential oil used in perfumery and phytotherapy. Despite its economic importance, the intra-specific diversity among wild, non-cultivated plants remains poorly understood. We analyzed the structure of the chemical and genetic diversity of plants from 14 sites sampled over the entire native range of the true lavender. Volatile organic compounds of inflorescences were analyzed using gas chromatography coupled to mass spectrometry. Genotyping was performed with fingerprinting genetic markers. To limit the influence of environmental variability on chemical composition, plants were grown in the same conditions in a common garden. Without prior knowledge, discriminant analysis of principal component identified unambiguously four distinct chemotypes among three genetic populations. Co-inertia analysis and supervised analysis which integrated multiple datasets indicated a strong congruency between chemical and genetic patterns. Two distinct genetic units were located at the edge of the distribution area in the south of Italy and in the northeast of Spain, and were associated with two distinct chemotypes. Our results confirmed the existence of three genetically distinct entities, suggesting speciation. All French populations and the Italian Piedmontese population were genetically homogeneous but separated in two distinct chemotypes. The dominant chemotype was present in the center of the native range in southeastern France and was at the origin of the current most cultivated French varieties. Its main compounds were linalyl acetate, linalool, and caryophyllene oxide. The second French chemotype was found in south of Massif Central and presented high abundance of valuable linalyl and lavandulyl acetates. Linalool, eucalyptol, β-caryophyllene, borneol, camphor, and cis-sabinene-hydrate were significantly associated with southern latitudes and their role would be worth exploring.